2016
DOI: 10.1177/0363546515622407
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Medial Ulnar Collateral Ligament Reconstruction

Abstract: The frequency of UCL reconstruction is steadily rising in New York State and becoming more common in adolescent athletes. Emphasis on public education on the risks of overuse throwing injuries and the importance of adhering to preventative guidelines is essential in youth baseball today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
152
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 28 publications
3
152
1
3
Order By: Relevance
“…Our sex-specific trends also showed varying agreement with previous findings. Hodgins et al 18 noted that male adolescents were 11.8 times more likely to undergo UCL reconstruction than female adolescents in their study, whereas our data demonstrated surgery was more likely in males with an odds ratio of 1.14 (P < .0005). In another study, Dodwell et al 11 found that male adolescents were 15% more likely to undergo ACL reconstruction as opposed to female adolescents, similar to our data.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Our sex-specific trends also showed varying agreement with previous findings. Hodgins et al 18 noted that male adolescents were 11.8 times more likely to undergo UCL reconstruction than female adolescents in their study, whereas our data demonstrated surgery was more likely in males with an odds ratio of 1.14 (P < .0005). In another study, Dodwell et al 11 found that male adolescents were 15% more likely to undergo ACL reconstruction as opposed to female adolescents, similar to our data.…”
Section: Discussioncontrasting
confidence: 76%
“…The aforementioned findings contradict the findings of other studies that have looked at trends in surgical intervention for sports injuries in youth and adolescent populations. 10,11,14,15,18 Dodwell et al 11 used the New York Statewide Planning and Research Cooperative System (SPARCS) database and identified an almost 3-fold increase in the incidence in ACL reconstruction among 25,315 patients from 3 to 20 years of age from 1990 to 2009. Werner et al 15 used the Pearl Diver database and also found that overall numbers of ACL injury diagnoses and reconstructions increased from e62 2007 to 2011, although incidence data were not available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Über 400 professionelle Baseballspieler haben zwischen 1998 und 2015 eine mediale Bandplastik erhalten, wobei die Anzahl der durchgeführten Operationen erst in den letzten Jahren deutlich zugenommen hatte [5]. Auch Hodgins et al [29] …”
Section: Medialer Bandkomplexunclassified